2008
DOI: 10.1177/1557988307311353
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Roles: Insights Into Issues for Men Caring for Family Members With Mental Illness

Abstract: Assumptions informing expectations of caring may not reflect the diversity of circumstances in which informal care is provided, and scant attention has been given to the experiences of men providing care to family members. This study reports on qualitative findings from a study that explored these issues among rural men caring for partners or children with a range of mental illnesses. The findings suggest that the primary relationship between carers and care recipients influences the ways in which the men unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…This could have been because of the love and responsibility they felt towards their son or daughter, giving meaning to both their fathering and caring role (McAuliffe et al, 2014). Fraser and Warr (2009) explored issues for men caring for family members with 'mental illness' and found that fathers in the sample never questioned the on-going care or responsibility of their child, in line with the current study. It could be understood as fathers wanting to maintain and uphold the crucial parts of their connection with their child and so extend the characteristic duties and responsibilities associated with parenting (Fraser & Warr, 2009).…”
Section: The Tensions In Being a Paternal Carersupporting
confidence: 74%
See 2 more Smart Citations
“…This could have been because of the love and responsibility they felt towards their son or daughter, giving meaning to both their fathering and caring role (McAuliffe et al, 2014). Fraser and Warr (2009) explored issues for men caring for family members with 'mental illness' and found that fathers in the sample never questioned the on-going care or responsibility of their child, in line with the current study. It could be understood as fathers wanting to maintain and uphold the crucial parts of their connection with their child and so extend the characteristic duties and responsibilities associated with parenting (Fraser & Warr, 2009).…”
Section: The Tensions In Being a Paternal Carersupporting
confidence: 74%
“…Fraser and Warr (2009) explored issues for men caring for family members with 'mental illness' and found that fathers in the sample never questioned the on-going care or responsibility of their child, in line with the current study. It could be understood as fathers wanting to maintain and uphold the crucial parts of their connection with their child and so extend the characteristic duties and responsibilities associated with parenting (Fraser & Warr, 2009). This links with the moral assumptions in how fathers feel they should act and potentially how people in their social network or community will view their actions (Wall & Arnold, 2007).…”
Section: The Tensions In Being a Paternal Carersupporting
confidence: 74%
See 1 more Smart Citation
“…In general, studies involving parents have often tended to focus more on mothers rather than fathers (e.g., Brannen & Nilsen, ; Brumariu & Kerns, ; Connell & Goodman, ). This could be because in Western society the majority of everyday parenting tasks are still more likely to be conducted by mothers than fathers, with mothers tending to be viewed as children's primary caregivers (Bianchi, ; Fraser & Warr, ), although national trends suggest a significant increase in fathers’ involvement in their children's lives since the 1970s (Bianchi, ; O'Brien & Shemilt, ). Thus, this could imply that unless one deliberately seeks equal representation of mothers and fathers in one's study of parents, which was not the case in the IMPACT trial or the IMPACT‐ME study, mothers may inevitably form the majority of such a sample.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested, however, that this carer role has been overlooked by health professions; an omission partly attributed to postpartum nursing's traditional focus on the mother and infant dyad rather than on a family perspective [ 9 - 11 ]. Others have found that care giving is also seldom associated with the traditional ideals of masculinity [ 12 , 13 ]. These authors determined that women with PPD nevertheless sought partners' or relatives' assistance to lessen their suffering and to assist them with functioning.…”
Section: Introductionmentioning
confidence: 99%